2013
DOI: 10.1104/pp.113.224162
|View full text |Cite
|
Sign up to set email alerts
|

The PYL4 A194T Mutant Uncovers a Key Role of PYR1-LIKE4/PROTEIN PHOSPHATASE 2CA Interaction for Abscisic Acid Signaling and Plant Drought Resistance      

Abstract: Because abscisic acid (ABA) is recognized as the critical hormonal regulator of plant stress physiology, elucidating its signaling pathway has raised promise for application in agriculture, for instance through genetic engineering of ABA receptors. PYRABACTIN RESISTANCE1/PYR1-LIKE (PYL)/REGULATORY COMPONENTS OF ABA RECEPTORS ABA receptors interact with high affinity and inhibit clade A phosphatases type-2C (PP2Cs) in an ABA-dependent manner. We generated an allele library composed of 10,000 mutant clones of Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
114
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(117 citation statements)
references
References 45 publications
3
114
0
Order By: Relevance
“…Stomatal size and densities were not different in the RCAR6 line from the wild type, indicating that the observed changes in transpiration reflect ABA signaling-mediated changes in apertures of stomata. This conclusion is in line with other studies in which ectopic ABA receptor expression caused ABAhypersensitive stomatal responses (18,(22)(23)(24).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Stomatal size and densities were not different in the RCAR6 line from the wild type, indicating that the observed changes in transpiration reflect ABA signaling-mediated changes in apertures of stomata. This conclusion is in line with other studies in which ectopic ABA receptor expression caused ABAhypersensitive stomatal responses (18,(22)(23)(24).…”
Section: Discussionsupporting
confidence: 82%
“…ABA perception recruits an ABA-binding REGULATORY COMPONENT OF ABA RECEPTOR (RCAR)/PYRABACTIN RESISTANCE 1 (PYR1)/PYR1-LIKE (PYL) and an associated protein phosphatase of type 2C (PP2C) (18, 19). Administration of ABA and ABA agonists (20, 21), ectopic expression of RCARs (17,18,[22][23][24], as well as reduced expression of PP2Cs (25) have been shown to minimize plant transpiration and, in some cases, to enhance survival under water deficit. It is clear that plants with strongly reduced transpiration are limited in CO 2 uptake and, hence, in growth and biomass formation.…”
mentioning
confidence: 99%
“…The crystal structure of RCAR7-PP2CA revealed an additional interaction domain provided by a zinc-finger domain present in PP2CA and HAImember PP2Cs (41), which might provide an explanation for the high affinity of PP2CA in vitro and the high efficiency of RCAR7 to antagonize PP2CA and HAI2 action on ABA signaling. Several studies identified amino acid residues of RCARs (7,14,40,46) that alter interaction with PP2Cs, but none have reported so far on successful alteration of PP2C to establish RCAR binding. For clade A PP2Cs, a number of mutations are known to reduce or obliterate the interaction with RCARs, which results in ABA-insensitive coreceptors such as the classical abi1-1 (ABI1 G180D ) and abi2-1 (ABI2 G168D ) proteins or mutations in the ABA-sensing tryptophan residue (7,8,39).…”
Section: Q386nmentioning
confidence: 99%
“…Subcellular localization studies indicate that PP2Cs are present at the nucleus and cytosol, which is in agreement with their reported interaction with SnRK2s (Fujita et al, 2009 or the slow anion channel 1 (SLAC1) and SLAC1 homolog 3 (SLAH3), and transcriptional regulators, such as bZIP transcription factors and chromatin-remodeling complexes (SWI2/SNF2) (Cherel et al, 2002, Guo et al, 2002, Lee et al, 2007, Saez et al, 2008, Geiger et al, 2009 conformations by contacting the PP2C domain of ABI1. This structural consideration explains that the interaction between ABI1 and RCAR1 (also known as PYL9), which is a member of the ABA Antoni et al, 2012, Brandt et al, 2012, Lynch et al, 2012, Pizzio et al, 2013, Rodrigues et al, 2013.…”
Section: Protein Phosphatases Type 2c Pp2csmentioning
confidence: 99%
“…PP2CA inhibits SLAC1 channel activity in two ways, due to direct interaction with SLAC and by dephosphorylation of the kinase OST1 leading to kinasedependent phosphorylation inhibition (Lee et al, 2009). Another study trying to elucidate implications of PP2CA in ABA signaling pathway came from Pizzio et al (2013). This work generated an allele library composed of 10,000 mutant clones of Arabidopsis PYL4 receptor where mutations that promoted ABA-independent interaction with PP2CA/AHG3 were selected.…”
Section: Aba Controls Kmentioning
confidence: 99%